Rationality economic and terrorism (2010)
This paper is more about economics as social science than about terrorism. The main argument is as follows. Once upon a time a creature called homo economicus went to war but shot himself in the foot (Cramer, 2002). In other words, the extension of neoclassical economics to 'explain' the causes of civil wars has thus far not been a great success in either theoretical or empirical terms. Then, returning wounded and vengeful from the front, homo economicus weighed up the costs and benefits of conflict versus cooperation, assessed the constraints, underwent some training in behavioural psychology, and made the rational choice to engage in terrorism, but she blew herself up accidentally. In other words, neo-classical economic explanations of terrorism are very interesting, in some ways more so than those explaining civil war, but they are selfdefeating in their efforts and they reveal the weaknesses of neo-classical economics as a foundation for social science.